2011
DOI: 10.1177/1073191111408230
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of the Structured Interview of Reported Symptoms in a Sample of Individuals With Intellectual Disabilities

Abstract: The challenges of accurate forensic assessment are aggravated when evaluatees have intellectual disabilities. Few studies have addressed the efficacy of forensic assessment in samples diagnosed with an intellectual disability, and those that have typically focus on measures of cognitive effort rather than on feigned psychiatric symptoms. This study focuses on the applicability of the original and revised versions of the Structured Interview of Reported Symptoms (SIRS) in a sample of participants with genuine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Although previous research has reported that individuals with an intellectual disability who are not suspected of malingering often score in the malingering range on malingering tests (Hayes et al, 1997;Hurley & Deal, 2006;Weiss et al, 2011), no research has examined the role of intelligence on performance on the ILK. Additionally, the majority of the research studying malingering and intelligence has focused solely on intellectual disabilities and not across the full range of IQ scores.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Although previous research has reported that individuals with an intellectual disability who are not suspected of malingering often score in the malingering range on malingering tests (Hayes et al, 1997;Hurley & Deal, 2006;Weiss et al, 2011), no research has examined the role of intelligence on performance on the ILK. Additionally, the majority of the research studying malingering and intelligence has focused solely on intellectual disabilities and not across the full range of IQ scores.…”
Section: Discussionmentioning
confidence: 97%
“…Many research participants with intellectual deficits score in the feigning range on malingering tests, even when instructed to perform optimally (Dean, Victor, Boone, & Arnold, 2008;Hayes et al, 1997;Hurley & Deal, 2006;Marshall & Happe, 2007;Weiss et al, 2011). Unfortunately, most of the studies examining malingering and intelligence use participants with an intellectual disability instead of those with a range of intellectual deficits.…”
mentioning
confidence: 93%
See 3 more Smart Citations